2013
DOI: 10.1002/14651858.cd003452.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic treatment for prominent upper front teeth (Class II malocclusion) in children

Abstract: Orthodontic treatment for prominent upper front teeth (Class II malocclusion) in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 103 publications
1
89
1
6
Order By: Relevance
“…Taken individually none of these studies found any difference in the incidence of trauma between those patients who had undergone early treatment and patients who had undergone comprehensive treatment in adolescence. [15][16][17] A recent systematic review has combined the results for the three studies and found a small, but statistically significant difference, with the early treatment group experiencing less trauma; 18 however the authors of one of the original studies noted that most of the trauma experienced was minor and in order to reduce the risk of trauma, orthodontic treatment would need to be started in the early mixed dentition stage, fairly soon after the maxillary incisors had erupted, in all children with an increased overjet. 15 Considering the greater financial burden it would incur to treat all these children, it is probably not cost effective in the majority of cases.…”
Section: Prevention Of Dentoalveolar Traumamentioning
confidence: 99%
“…Taken individually none of these studies found any difference in the incidence of trauma between those patients who had undergone early treatment and patients who had undergone comprehensive treatment in adolescence. [15][16][17] A recent systematic review has combined the results for the three studies and found a small, but statistically significant difference, with the early treatment group experiencing less trauma; 18 however the authors of one of the original studies noted that most of the trauma experienced was minor and in order to reduce the risk of trauma, orthodontic treatment would need to be started in the early mixed dentition stage, fairly soon after the maxillary incisors had erupted, in all children with an increased overjet. 15 Considering the greater financial burden it would incur to treat all these children, it is probably not cost effective in the majority of cases.…”
Section: Prevention Of Dentoalveolar Traumamentioning
confidence: 99%
“…30,31 In particular, optimal timing for functional/ orthopedic treatment for skeletal Class II and Class III has been reported to be late [32][33][34] and early, 2 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, contrasting recommendations have been carried out from current research regarding the reliability of such methods. 3,4 Studies on the radiographical growth indicators are essentially of two types: the ones correlating the various stages of maturation with mandibular growth spurt, 5 and the ones evaluating skeletal effects obtained by functional treatment in Class II patients the timing of treatment has been based on such indicators (for review, see Perinetti et al 4 ) Interestingly, while many of the former types of investigations reported poor correlation between the stages of growth indicators (mainly the CVM) and mandibular growth spurt, 6 most of the latter type of investigations reported clinically relevant favourable effects when the growth indicators are used. 4 It is perhaps that investigations are still missing the relevant piece of evidence.…”
Section: Clinical Articlementioning
confidence: 99%